Áudio-imagem: estudo da comunicação auditiva segundo Joachim-Ernst Berendt - Amaral, Luiza Spínola (2016)
The purpose of this research is to make a critical analysis about the literary and media work of the Germany radio man and jazz specialist, Joachim-Ernst Berendt. The focus is on the second stage of his career, no long dedicated to music, but to sounds and to hear, with the proposal to elaborate the concept of "audio-image". For this, he proposes a corpus that is composed by the radio masterpiece and then book "Nada Brahma – Die Welt ist Klang" (called "Nada Brahma: o mundo e o universo da consciência" in the Brazilian edition). With the justification that the visual images do not seduces the glances anymore due to the high speed of dissemination in contemporary cultural environments, this thesis investigates another approach about the image, able to contribute to a theory of audio images, which looks very necessary due to sound obscuring in the profusion of audio-visual media. In this sense, in addition to present the ideas of the German author in the domain of the communication's research in Brazil, this thesis defines the hearing experience as a resistance strength against the hegemony of visual images. Thus, it approaches the thought of Berendt to the Dietmar Kamper one, both in dialog with the thought of Norval Baitello Jr. in his theory of the image and culture. As his own reference, Baitello Jr. presents Berendt, extending the dialog with other thinkers as Harry Pross, which includes the body in its sensorial perception as primary media in its media classification, and Kamper himself, when announces the return to the hearing as a way of combating the "suffering" of the eyes. Thereby, the thesis proposes a concept of sound image close to a science called, by Hans Belting, "Anthropology of Image", where the sound appears as a vehicle of culture. For an understanding of the sounds and the media, the research uses the work of musicologists and sound engineers R. Murray Schafer and Michel Chion, which do not reduce the understanding of sound to the field of tradition of music. The theoretical framework also includes the authors cited by Berendt and his commentators, like the philosopher Peter Sloterdijk, the historians Andrew Right Hurley and Uta G. Poiger, in addition to the maestro and musicologist Julio Medaglia. We propose therefore a reflection about the restoration of relations and links broken in the light of the new culture of media